2010
DOI: 10.1103/physreva.82.063401
|View full text |Cite
|
Sign up to set email alerts
|

Spin nutation induced by atomic motion in a magnetic lattice

Abstract: An atom moving in a spatially periodic field experiences a temporary periodic perturbation and undergoes a resonance transition between atomic internal states when the transition frequency is equal to the atomic velocity divided by the field period. We demonstrated that spin nutation was induced by this resonant transition in a polarized rubidium (Rb) atomic beam passing through a magnetic lattice. The lattice was produced by current flowing through an array of parallel wires crossing the beam. This array stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Besides, with the development of the laser-cooling technique, the slow-moving atoms can be obtained easily. Therefore, some interesting researches on atomic motion have been carried out [29][30][31][32][33][34]. These researches have shown that the atomic motion and the field-mode structure can bring about the nonlinear transient effects of atomic population [29], control the entanglement and realize the quantum gate operation [30], influence quantum fluctuations of a single atom in a weakly driven cavity [31], and suppress the Rabi oscillations of an atom irradiated by a laser in resonance with the atomic transition [32].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, with the development of the laser-cooling technique, the slow-moving atoms can be obtained easily. Therefore, some interesting researches on atomic motion have been carried out [29][30][31][32][33][34]. These researches have shown that the atomic motion and the field-mode structure can bring about the nonlinear transient effects of atomic population [29], control the entanglement and realize the quantum gate operation [30], influence quantum fluctuations of a single atom in a weakly driven cavity [31], and suppress the Rabi oscillations of an atom irradiated by a laser in resonance with the atomic transition [32].…”
Section: Introductionmentioning
confidence: 99%
“…As an attempt to increase N, MIR was tested with an Rb atomic beam travelling between wire currents that generated a periodic magnetic field for N = 28 [17] and 10 [18]. The relative linewidths were observed as 4% and 10%, respectively, as expected.…”
Section: Introductionmentioning
confidence: 58%
“…A schematic diagram of the experimental setup is shown in figure 1. The setup was the same as the one used in a previous experiment [11], with the exception of the use of a transmission grating instead of a magnetic lattice made of current-carrying wires. Specifically, a Rb atomic beam emerged from an oven heated to nearly 200 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Sharp resonance lines, limited by the transit time, were obtained in an atomic beam experiment [10]. Coherent manipulation of the atomic spin through motion-induced resonance has also been demonstrated [11].…”
Section: Introductionmentioning
confidence: 95%